PENGELOLAAN PERMINTAAN DAN KAPASITAS PRODUKSI UMKM DI KOTA BATAM (SAHABAT TAICHAN BATAM) - Shofiy Shofiyah; Aisyah Fitriana; Inayah Alifia Fajar; Tiara Maharani; James Valentino; Vera Edelia Lim; Selvia Zulastri (MANAJEMEN, 2022)
Currently, the development of business in Indonesia is very rapid, especially in the culinary or food sector. This increase phenomenon is based on one of the government's roles in efforts to improve the impact of the COVID-19 pandemic, namely the Micro, Small and Medium Enterprises (MSME) empowerment program. UMKM Sate Sahabat Taichan Batam has the opportunity to develop even better. The purpose of this research is to optimize the production process of UMKM Sate Sahabat Taichan Batam in accordance with the capacity and demand of consumers so that SMEs can predict how much demand for products with separate requests for the future as well as service orders given and the total demand for these products can be known. The data collection method that we use is to conduct interviews so that we can directly get information orally and can get clear data about research problems. The results of the research that the author examines that the pattern of demand from year to year continues to increase for the product. Therefore, with the pattern of product demand that is increasing from consumer demand, the profits obtained by MSME owners are also increasing and the development of branch outlets helps overcome consumer demand.